Simultaneous Measurements of Substorm‐Related Electron Energization in the Ionosphere and the Plasma Sheet. Issue 10 (13th October 2017) - Sivadas, N.; Semeter, J.; Nishimura, Y.; Kero, A.
Abstract: On 26 March 2008, simultaneous measurements of a large substorm were made using the Poker Flat Incoherent Scatter Radar, Time History of Events and Macroscale Interactions during Substorm (THEMIS) spacecraft, and all sky cameras. After the onset, electron precipitation reached energies ≳100 keV leading to intense D region ionization. Identifying the source of energetic precipitation has been a challenge because of lack of quantitative and magnetically conjugate measurements of loss cone electrons. In this study, we use the maximum entropy inversion technique to invert altitude profiles of ionization measured by the radar to estimate the loss cone energy spectra of primary electrons. By comparing them with magnetically conjugate measurements from THEMIS‐D spacecraft in the nightside plasma sheet, we constrain the source location and acceleration mechanism of precipitating electrons of different energy ranges. Our analysis suggests that the observed electrons ≳100 keV are a result of pitch angle scattering of electrons originating from or tailward of the inner plasma sheet at 9 R E, possibly through interaction with electromagnetic ion cyclotron waves. The electrons of energy 10–100 keV are produced by pitch angle scattering due to a potential drop of ≲10 kV in the auroral acceleration region (AAR) as well as wave–particle interactions in and tailward of the AAR. This work demonstrates the utility of magnetically conjugate ground‐ and space‐based measurements in constraining the source of energetic electron precipitation. Unlike in situ spacecraft measurements, ground‐based incoherent scatter radars combined with an appropriate inversion technique can be used to provide remote and continuous‐time estimates of loss cone electrons in the plasma sheet. Plain Language Summary: On the night of 26 March 2008 in Alaska, the sky lit up with intense auroral activity. A ground‐based electronically steerable radar and a spacecraft were simultaneously monitoring this activity. The radar observed intense signatures of charged particle density at unusually low altitudes (<70 km), suggesting that unusually high‐energy electrons were raining down from the magnetosphere. Although numerous studies in the past have estimated the source population of electrons, it has been difficult to determine and separate contributions from different physical processes. In this study, we deduced the energy and number of these electrons using radar measurements of charged particle density as a function of altitude. By comparing this estimate with that measured by the spacecraft along the same magnetic field line, we identified the source location and mechanism of acceleration of electrons of different energies. Our analysis suggests that the observed high‐energy electrons are accelerated at distances beyond 60, 000 km from the Earth by interacting with electromagnetic waves, whereas lower energy electrons are mostly accelerated by electric fields much closer to Earth. Our study demonstrates the utility of combining radar and spacecraft measurements in determining the source region and acceleration process of these high‐energy electrons. Key Points: Subrelativistic electron precipitation ≳100 keV observed using incoherent scatter radar during a substorm Source of the precipitating subrelativistic electrons lies at or tailward of the inner plasma sheet Incoherent scatter radar can measure energy spectra of precipitating magnetospheric plasma